Mountaintop removal coal mining impacts on structural and functional indicators in Central Appalachian streams - Burke, Roger A.; Fritz, Ken M.; Johnson, Brent R.; Price, Rachel (Frontiers in Water, 2023)
Mountaintop removal coal mining (MTR) has been a major source of landscape change in the Central Appalachians of the United States (US). Changes in stream hydrology, channel geomorphology and water quality caused by MTR coal mining can lead to stream impairment. The objective of the Clean Water Act (CWA) is to restore and maintain the ecological integrity of the Nation’s waters. Sensitive, readily measured indicators of ecosystem structure and function are needed for the assessment of stream ecological integrity. Most such assessments rely on structural indicators; inclusion of functional indicators could make these assessments more holistic and effective. The goals of this study were: (1) test the efficacy of selected carbon (C) and nitrogen (N) cycling and microbial structural and functional indicators for assessing MTR coal mining impacts on streams; (2) determine whether indicators respond to impacts in a predictable manner and (3) determine if functional indicators are less likely than structural indicators to change in response to MTR coal mining. Seasonal measurements were conducted over the course of a year in streams draining small MTR-impacted and forested watersheds in the Twentymile Creek watershed of West Virginia (WV). Five of eight structural parameters measured had significant responses, all means greater in MTR-impacted streams than in forested streams. These responses resulted from changes in source or augmentation of the original source of the C and N structural parameters because of MTR coal mining. Only three of the fourteen functional indicators measured responded to MTR coal mining, all means greater in forested streams than in MTR-impacted streams. These results suggest that stressors associated with MTR coal mining caused reduction in microbial cycling, but resource subsidies may have counterbalanced some inhibition leading to no observable change in most functional indicators. The detritus base, thought to confer functional stability, was likely sustained in the MTR-impacted streams by channel storage and/or leaf litter inputs from largely intact riparian zones. Overall, our results largely support the hypothesis that certain functional processes are more resistant to stress induced change than are structural properties but also suggest the difficulty of identifying suitable functional indicators for ecological integrity assessment.